Empowering adolescent cadres for promoting oral health behavior: A persuasive communication training pilot study in Indonesia - Setiawan, Arlette Suzy; Pratidina, Naninda Berliana; Budiarto, Arief; Sukmasari, Susi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: Adolescents are considered good cadres to be able to socialize with this healthy dental behavior. Therefore, designing a dental health education program is necessary to prepare adolescents to socialize with dental health behavior. Purpose: This study evaluates the pilot training for trainers using persuasive communication to socialize dental health behavior. Methods: Thirty-five participants (13-16 years old) are trained by a persuasive communication coach and practice the skills with a simulated client”this one-day training has a two-phase structure; lectures and practicum. The evaluation is done through three out of four-level methods from Kirkpatrick (1959). The data analysis used for the reaction evaluation is descriptive statistics, calculating the average score per category of training support assessment items (curriculum, facilitator, accommodation, and overall score). The learning outcome analysis resulted from an analysis of the pre-post test results using the N-Gain value and paired T-test. Behavior outcomes were also analyzed descriptively by calculating the average score of all participants in every timeline (baseline and two weeks after the training). Results: evaluation of this training revealed that